Green Synthesis and Characterization of Silver Nanaoparticles by Aerial Parts of Achyranthes Aspera Linn - Fathima, Syed Ali; Vijayasanthi, M.; Doss, A. (Asian Journal of Science and Applied Technology, 2016)
The present study pacts with synthesis and characterization of silver nanaoparticles using aqueous extract of Achyranthes aspera. The synthesis of silver nanaoparticles was analyzed by changes of colour from greenish to reddish brown and it indicates the formation of silver nanoparticles. The nanoparticle was also characterized by Surface Plasmon Resonance through UV- Visible spectroscopic analysis. A methodical characterization of silver nanoparticles was performed using UV, SEM, FTIR, EDAX and antibacterial activities. Antibacterial activity shown by synthesized silver nanoparticles against microbial pathogens such as Pseudomonas aeruginosa, Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae and E.coli by agar well diffusion method. The significant antibacterial was observed.